2005
DOI: 10.1557/mrs2005.100
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Materials for Surface-Enhanced Sensing and Spectroscopy

Abstract: Localized surface plasmon resonance (LSPR) excitation in silver and gold nanoparticles produces strong extinction and scattering spectra that in recent years have been used for important sensing and spectroscopy applications. This article describes the fabrication, characterization, and computational electrodynamics of plasmonic materials that take advantage of this concept.Two applications of these plasmonic materials are presented: (1) the development of an ultrasensitive nanoscale optical biosensor based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
552
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 642 publications
(569 citation statements)
references
References 49 publications
5
552
0
4
Order By: Relevance
“…Another important aspect of noble NPs, when dispersed in a dielectric matrix, is that their optical response strongly depends on their clustering tendency, namely the clusters size, shape and distribution [3,35,36], the interaction between them [7,37], but also on the host matrix dielectric function itself [11,[38][39][40][41].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Another important aspect of noble NPs, when dispersed in a dielectric matrix, is that their optical response strongly depends on their clustering tendency, namely the clusters size, shape and distribution [3,35,36], the interaction between them [7,37], but also on the host matrix dielectric function itself [11,[38][39][40][41].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Since changes in size, shape and distribution of Au clusters are fundamental parameters for tailoring of the LSPR effect [1][2][3]36], a set of films with a wide range of Au concentration was prepared. The films were deposited by direct current (DC) magnetron sputtering, and in order to promote the clustering of the Au nanoparticles, the as-deposited samples were subjected to an in-air annealing protocol.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…As known, the plasmonic effect only happens in a localized area (generally less than 100 nm) near the dielectric/metal interface. [ 49 ] The alignment of the LC molecules inside and outside the annular aperture could play a signifi cant role in photoinduced refractive index modulation, thus affecting the transmittance of the whole device. Crawford et al have investigated the molecularanchoring properties of the nematic LCs in cylindrical cavities and found that an escaped radial with singular point defects (ERPD) alignment was preferably supported for an untreated cavity with its radius larger than 50 nm.…”
Section: Op133mentioning
confidence: 99%
“…Production of hollow Au nanocrystals with faceted geometry allows increased tunability of optical properties as the surface plasmon resonance spectra of a hollow metallic nanocrystal depends strongly not only on the shell thickness, but also on the detailed shape. 16,17 To produce Ag nanocrystals with reduced sizes and improved monodispersity, we performed the synthesis using a modification of the polyol process in an organic solvent and at high temperature. 6,18 The silver salt AgNO 3 was reduced by a long chain polyol such as 1,2-hexadecanediol using an organic solvent, o-dichlorobenzene (DCB).…”
mentioning
confidence: 99%